The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/00365548.2013.847531
|View full text |Cite
|
Sign up to set email alerts
|

Cellulomonas, an emerging pathogen: A case report and review of the literature

Abstract: Cellulomonas is a rare but emerging human pathogen, causing infection in only 4 reported cases in the literature. We present the first case of ascending cholangitis with Cellulomonas bacteremia and sepsis, as well as a brief review of the literature. We summarize every case of Cellulomonas reported in the medical literature, including treatments and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Mycobacterium related CIED infection was rarely found. There were case reports both from Asian and western countries . The most common isolated Mycobacterial organisms were in the M. fortuitum group, which account for approximately 50% of mycobacterial infections .…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium related CIED infection was rarely found. There were case reports both from Asian and western countries . The most common isolated Mycobacterial organisms were in the M. fortuitum group, which account for approximately 50% of mycobacterial infections .…”
Section: Discussionmentioning
confidence: 99%
“…A published study of Lagier et al [27] noted that the Cellulomonas strain obtained spectrum did not match with any of the 11 spectra contained in the database. On the other hand, Marko et al [28] have successfully identified one Cellulomonas strain to the genus and species level by MALDI-TOF-MS. Cellulomonas genus was originally thought to be an opportunistic infection. However, 5 clinical cases were reported in immune-competent adults [29].…”
Section: Strains Identified By Api Corynementioning
confidence: 99%
“…Mycobacteria and especially M. marinum are well‐known causes of disease in humans through contact with fish and the aquatic environment (Sunil et al, ; Thirunavukkarasu, Plain, de Silva, Marais, & Whittington, ; Verner‐Jeffreys et al, ). To the best of our knowledge, M. goodii has not been detected in fish to date; on the contrary, it is an emerging nosocomial human pathogen (Salas & Klein, ).…”
Section: Discussionmentioning
confidence: 99%